(untitled) (Medical Forum Monthly, 2022)
Objective: To check whether Non-Alcoholic Fatty Disease of Liver and Pancreas have same implications / significance in Type 2 Diabetes and Obesity? Study Design: Observational / cross section study Place and Duration of Study: This study was conducted at the Department of Medicine,.Rai Medical College, Sargodha from April to December 2021. Materials and Methods: This study was carried out on the patients presenting in medical College, from 40 to 70 years of age, both genders. Obesity was assessed by the simplest and most practiced parameter of obesity as “Looking Obese” or having a “sacking or protuberant tummy”. Type 2 Diabetes Mellitus (T2DM) was confirmed on the basis of available blood sugar and HbA1c record. After applying inclusion (obesity and T2DM) and exclusion criteria, volunteering participants were asked to get an abdominal ultrasound (USG) examination for grading of Hepatic Parenchymal Echogenicity (HPE) Grades (G1-G3) in NAFDL and to measure Pancreatic Parenchymal Echogenicity (PPE), Grades (G0-G3) in NAFDP through the same acoustic window. Results: 490 females and 217 males who volunteered to participate were included in this study. There were 315 females exhibiting G1 HPE, out of these 27% had G0 NAFDP, 9% had G1 NAFDP, 60% had G2 NAFDP and 4% had G3 NAFDP. There were 175 females exhibiting G2 HPE, out of these 36% had G0 NAFDP, 24% had G1 NAFDP, 32% had G2 NAFDP and8% had G3 NAFDP. No female had G3 HPE. Out of a total of 217 males, there were 119 males exhibiting G1 HPE, out of these 71% had G0 NAFDP, 18% had G1 NAFDP, 12% had G2 NAFDP and none had G3 NAFDP. There were 98 males exhibiting G2 HPE, out of these 50% had G0 NAFDP, 14% had G NAFDP, 29% had G2 NAFDP and 7% had G3 NAFDP. No male had G3 HPE. Conclusion: USG is most cost-effective due to its wide availability, reliability in diagnosing and reproducibility in following changes both for better or worse, being cheap and non-invasive nature makes it ideal for early diagnosis of HPE in NAFDL and NAFDP. Early detection of HPE changes and sensitization to its future implication as a risk factor for metabolic syndrome (mainly diabetes and obesity), CLD and even HCC among both medical community and general public must be the priority in our professional circles. It shall be highlighted in all clinical conferences because early interventions in terms of lifestyle modifications targeted to not only weight reduction but more importantly weight maintenance have a great potential for reversal of all these changes.